Profiling of the Contents of Amino Acids, Water-Soluble Vitamins, Minerals, Sugars and Organic Acids in Turkish Hazelnut Varieties - Taş Neslihan Göncüoğlu; Gökmen Vural (Polish Journal of Food and Nutrition Sciences)
Proximate composition, profiles of amino acids, sugars, organic acids, vitamins and minerals of fourteen Turkish hazelnut varieties harvested in 2013 and 2014 were investigated. Glutamic acid, arginine and aspartic acid were the most predominant amino acids, representing of about 50% of hazelnut protein. Individual amino acid profiles showed significant differences depending upon the harvest year (p<0.05). Concentration of sucrose was the highest followed by fructose, glucose, stachyose, raffinose and myo-inositol, respectively. Phytic acid was predominant organic acid in all varieties, followed by malic acid. Independent of the variety, hazelnuts were rich in pantothenic acid, nicotinic acid, pyridoxal, biotin, thiamine, nicotinamide. Pantothenic and nicotinic acid were significantly higher in most of the varieties in harvest year 2014. Potassium was the most predominant mineral, followed by magnesium, calcium, sodium, manganese, zinc, iron and copper, respectively.